Polishing Diamonds or Quixoticism: the Role of the Foreign Language Teacher Through the Lens of Metaphors - Jazbec, Saša; Kacjan, Brigita (Sodobni didaktični diskurzi v kontekstu pedagoške tradicije: Monografija v počastitev 80-letnice prof. dr. Martina Kramarja, 2025)
The only constant in the role of a (foreign language) teacher is continual change. This paper examines the evolving role of the foreign language teacher by first considering dominant methods of language learning and teaching, and then analyzing these through metaphors used by teachers and students to purposefully and consciously describe the profession. Metaphors are regarded not merely as stylistic embellishments or vivid language, but as fundamental cognitive tools that allow individuals to articulate their worldview and to comprehend the perspectives of others. Our focus is on the mental models these metaphors suggest. Specifically, we investigate whether the metaphors collected reflect a traditional, instruction-centered understanding of the foreign language teacher’s role, or whether they point toward a more contemporary, constructivist view of teaching and learning.